1972
DOI: 10.1126/science.177.4046.353
|View full text |Cite
|
Sign up to set email alerts
|

Rare-Earth Oxides of Manganese and Cobalt Rival Platinum for the Treatment of Carbon Monoxide in Auto Exhaust

Abstract: The perovskite-like compounds RE(1-X)Pb(5)MnO(3) and RECoO(3), where RE (rare earth) is lanthanum, praseodymium, or neodymium, are active catalysts for the oxidation of carbon monoxide. Crushed single crystals of these compounds compare favorably with commercial platinum catalysts in initial activity and lifetime. Therefore, these compounds are promising substitutes for platinum in devices for the catalytic treatment of auto exhaust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
2

Year Published

1974
1974
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(87 citation statements)
references
References 3 publications
2
83
0
2
Order By: Relevance
“…Data show that LaMnO3 and LaCoO3 were the most active catalysts, while LaFeO3 was the less performing one, in spite of its higher lowtemperature activity through the suprafacial mechanism ( Fig.1), as previously observed [6,7,[16][17][18].…”
Section: -Effect Of the Nature Of B Metal On Activity And Resistancesupporting
confidence: 58%
“…Data show that LaMnO3 and LaCoO3 were the most active catalysts, while LaFeO3 was the less performing one, in spite of its higher lowtemperature activity through the suprafacial mechanism ( Fig.1), as previously observed [6,7,[16][17][18].…”
Section: -Effect Of the Nature Of B Metal On Activity And Resistancesupporting
confidence: 58%
“…Already, in 1971, LaCoO 3 perovskite-type oxide was proposed as an economic substitute for noble metal-based exhaust after treatment catalysts [6]. Co-, Fe-, Mn-, and Ru-based perovskite-type oxides exhibited promising activity for the oxidation of CO and the reduction of NO x [7][8][9][10][11]. La 0.8 Sr 0.2 CoO 3 was shown to compare well with 1 wt% Pt/Al 2 O 3 for hydrocarbon oxidation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Meadowcroft first reported the use of perovskite-type oxides as catalysts in 1970 9 for the electrochemical reduction of oxygen. Soon after that, Voorhoeve et al 10 reported the high catalytic activity of perovskite oxides for heterogeneous oxidation. These studies triggered many other works.…”
Section: Introductionmentioning
confidence: 99%